2015
DOI: 10.1186/s12978-015-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in receptivity epithelial cell markers of endometrium after ovarian stimulation treatments: its role during implantation window

Abstract: BackgroundTo compare the expression of receptivity markers in epithelial and stromal cells in the endometrium of ovulatory women and infertile with hypothalamic pituitary dysfunction (HPD), untreated or treated with clomiphene citrate (CC), or with recombinant follicle stimulating hormone (rFSH).MethodsTwelve control ovulatory and 32 anovulatory women, 22 of whom received ovulation induction with CC (n = 12) or rFSH (n = 10). Endometrial biopsies were obtained during the mid-secretory phase. Hormonal secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
(55 reference statements)
0
6
0
2
Order By: Relevance
“…Endometrial epithelial cells line the uterine lumen and glands, with the latter derived from the former [37, 38]. The endometrial epithelium undergoes dramatic cellular and molecular changes common to both mice and humans during the WOI, including adhesion mechanisms enabling the attachment of embryo to the luminal epithelium [39, 40], alterations in nuclear pore complex presentation [41], downregulation of the Serum and Glucocorticoid Regulated Kinase 1 (SGK1) [42], apoptotic cascade [43, 44], and expression of epithelial-specific receptivity markers [45]. The glandular epithelium further facilitates implantation via the production of Leukemia Inhibitory Factor (LIF), a critical factor in embryo-uterine communication during WOI [4648].…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial epithelial cells line the uterine lumen and glands, with the latter derived from the former [37, 38]. The endometrial epithelium undergoes dramatic cellular and molecular changes common to both mice and humans during the WOI, including adhesion mechanisms enabling the attachment of embryo to the luminal epithelium [39, 40], alterations in nuclear pore complex presentation [41], downregulation of the Serum and Glucocorticoid Regulated Kinase 1 (SGK1) [42], apoptotic cascade [43, 44], and expression of epithelial-specific receptivity markers [45]. The glandular epithelium further facilitates implantation via the production of Leukemia Inhibitory Factor (LIF), a critical factor in embryo-uterine communication during WOI [4648].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of endometrial receptivity have shown changes in the expression of epithelial receptivity markers during the mid-secretory phase in women using CC for ovulation induction, and these changes are believed to account for the lower-than-expected pregnancy rates in these women. 26 Endometrial thickness has been considered a surrogate marker of endometrial receptivity. 10,11 We hypothesized that the thinning effect of CC on the endometrium would be less significant in women who did not have a withdrawal bleed than in women who took MPA and had a withdrawal bleed.…”
Section: Cycle 1 (N = 14)mentioning
confidence: 99%
“…Cadherin is one of adhesion molecules expressed in glandular and luminal epithelia. Through a calciumdependent mechanism, E-cadherin maintains bonds between cells [29].…”
Section: E-cadherin As a Marker Of Endometrialmentioning
confidence: 99%